Badania możliwości technicznych pomiaru płaskości powierzchni kinematyczną metodą trygonometryczną = Researches on technical possibilities of flatness examination using kinematic trigonometric method - Wyczałek, Ireneusz; Plichta, Artur; Wyczałek, Michał (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
The new approach for measuring the flatness of floors or other horizontal surfaces is based on the use of vehicle-mounted sensors that moves through these surfaces in a more or less automated way. It becomes competitive in relation to the classical methods using the straightedge and the wedge or tilts or geodetic methods used interchangeably.
Keywords: płaskość; tachimetr zmotoryzowany; pomiar kinematyczny; flatness; motorized tachimetr; kinematic measurement